ХОРИЖИЙ ТИЛЛАРНИ ЎҚИТИШДА ЁШЛАРДА ЭСТЕТИК ДУНЁҚАРАШНИ ШАКЛЛАНТИРИШНИНГ ПЕДАГОГИК АСОСЛАРИ (Scientific journal of the Fergana State University, 2023)
This article describes methods of forming aesthetic outlook of young people in teaching foreign languages. In addition to enriching the students' knowledge of foreign languages, the issues of forming aesthetic education and aesthetic outlook have been analyzed. Also, the author talks about interactive methods of foreign language use in strengthening communication with different nationalities, and demonstrating national traditions.